The Pricing of Bank Debt Guarantees - Stefan Arping (Tinbergen Institute, 2009)
We analyze the optimal pricing of government-sponsored bank debt guarantees within the context of an asset substitution framework. We show that the desirability of fair pricing of guarantees depends on the degree of transparency of the banking sector: in relatively opaque banking systems, fair pricing exacerbates banks' incentive to take excessive risks, whereas the opposite is true in relatively transparent banking systems.
Keywords: G21; G38; 330; Debt Guarantees; Fair Pricing; Financial Stability; Bankgarantie; Risikoprämie; Kreditrisiko; Moral Hazard; Bankenkrise; Theorie